«El Evangelio puede matar» Análisis del preámbulo hermenéutico de la anti-cristología de Juan Luis Segundo - Celli, María Eugenia (Veritas, 2013)
Contemporary men and women are not exempt form that Pauline warning about «letter that gives death». Latin American liberation theologian, Juan Luis Segundo S. J., has sensibly and brilliantly detected this imminent danger in his contemporaries access to gospel and, through it, to Jesús of Nazareth’s figure. In view of such problems and in order to update a liberating Gospel, he decides to elaborate, in his principal christological work «El Hombre de hoy ante Jesús de Nazaret», an extensive hermeneutic preamble. Such preamble is this article’s object of analysis, to which we dedicate with the purpose of systematizing the complex hermeneutic task that he proposes and to establish the originaliy of his theological work, understood as anti-christology.